Analisis Pengendalian Kualitas Produksi Donat Di Toko Donat Madu Cihanjuang Kota Bekasi, Jawa Barat - Hadid Pangestu, Arya; Thoriq, Muhammad; Al Gifari Abdullah, Qeis; Paduloh, Paduloh (Jurnal Etnik: Ekonomi-Teknik, 2023)
This research aims to help reduce defects and improve the production process for the better. The method used in the Quality Control Analysis of Donut production is the Statistical Quality Control (SQC) method to ensure the level of product quality statistically, and by using a quantitative approach in the form of descriptive by collecting data through observation and interview techniques. Since the results of the data found did not exceed the threshold on the P control map with a centre line of 0.036, the results showed that the honey donut products were still within the statistical control limits. A number of variables, such as the influence of people, machines, and methods, have an impact on the cause of product failure. The recommended corrective action is to organise regular meetings to discuss improving the quality of honey donut products, which will be the main reason in determining the most important thing to improve the quality of production.